Growth Optimization Conditions for the Production of Fibrinolytic Enzyme from Ganoderma lucidumï€ - C. Chellaram1, T. Prem Anand1; V. Kaviyarasan 2*, S. Kumaran1, L.K. Jagadish2, P. Palani2, (Journal of Ecobiotechnology, 2010)
<span style="font-size: 10pt; line-height: 110%; font-family: ";Garamond";,";serif";; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">Ganoderma lucidum<span style="font-size: 10pt; line-height: 110%; font-family: ";Garamond";,";serif";; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;"> collected and isolated from south eastern part of India screened to produce fibrinolytic enzyme was conserved under laboratory condition to stablize or enhance the enzyme production. The fibrinolytic enzyme producing mushroom Ganoderma lucidum was grown under different pH, temperature, carbon and nitrogen sources to optimize the growth conditions required for enzyme production. The optimized conditions for fibrinolytic enzyme production was found to be pH at 5.5 (106 U/g. w.wt), Temperature at 30Â°C (88.17 U/g. w.wt), Carbon source - Glucose (143.43 U/g. w.wt) and Nitrogen source- Peptone (162.17 U/g. w.wt). <span style="font-size: 10pt; line-height: 110%; font-family: ";Garamond";,";serif";; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">——————————————————————————————————– <span style="font-size: 10pt; line-height: 110%; font-family: ";Garamond";,";serif";; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;"> 1Department of Biomedical Engineering, Veltech Â Multi TechDr. Rangarajan Dr. Sakunthala Engineering College, Chennai- 6000 61, India 2Center for Advanced Studies in Botany, University of Madras, Guindy Campus, Chennai â€“ 6000 62, India *Corresponding author, Email: kumaran.1331@gmail.com Tel: +91-9840064350; Fax: +91 044 22352494 Please Cite This Article As: Â S. Kumaran, L.K. Jagadish, P. Palani, C. Chellaram, T. Prem Anand and V. Kaviyarasan. 2010. Growth Optimization Conditions for the Production of Fibrinolytic Enzyme from Ganoderma lucidum. J. Ecobiotechnol. 2(4):11-15. Â